2014
DOI: 10.1016/j.bpj.2014.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Exciting Cell Membranes with a Blustering Heat Shock

Abstract: Brief heat shocks delivered to cells by pulsed laser light can evoke action potentials in neurons and contraction in cardiomyocytes, but the primary biophysical mechanism has been elusive. In this report we show in the neuromuscular junction of Caenorhabditis elegans that application of a 500°C/s heat shock for 500 μs evoked ~35 pA of excitatory current and injected ~23 fC(femtocoulomb) of charge into the cell while raising the temperature only 0.25°C. The key variable driving the current was the rate of chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 23 publications
6
70
1
Order By: Relevance
“…What remains unclear is how this transient heating elicits membrane depolarization of neurons and action potentials. Several mechanisms of action have been suggested, including the generation of transient capacitive currents [14,17], the stimulation of temperature sensitive ion channels [15,16], the generation of small pores in the plasma membrane [20] or the generation of laser-generated pressure pulses [18]. Our results show that IR laser pulses depolarize DRG neurons without the involvement of thermo-sensitive TRPV channels since the use of ruthenium red, a general blocker of TRP channels did not modify the depolarization amplitude.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…What remains unclear is how this transient heating elicits membrane depolarization of neurons and action potentials. Several mechanisms of action have been suggested, including the generation of transient capacitive currents [14,17], the stimulation of temperature sensitive ion channels [15,16], the generation of small pores in the plasma membrane [20] or the generation of laser-generated pressure pulses [18]. Our results show that IR laser pulses depolarize DRG neurons without the involvement of thermo-sensitive TRPV channels since the use of ruthenium red, a general blocker of TRP channels did not modify the depolarization amplitude.…”
Section: Discussionmentioning
confidence: 60%
“…Infrared laser pulses have been shown to induce intracellular calcium transients implicating mitochondria in neonatal cardiomyocytes [10] and in neonatal spiral and vestibular ganglion neurons [11] and to depolarize membranes in HEK293 cells [12], dorsal root ganglion neurons [13], oocytes, HEK cells and artificial layers [14], retinal and vestibular primary neurons [15,16], hippocampal neurons [17], spiral ganglion neurons [18], brain slices [19] and in vestibular hair cells and afferent neurons [20]. What remains unclear is whether an universal photothermal mechanism exists and how the transient heating induced by the IR laser pulse elicits membrane depolarization of neurons and action potentials or modulates intracellular signalling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shapiro et al [16] showed that these rapid temperature variations are directly accompanied by changes in the cell membrane's capacitance and resulting displacement currents which are unrelated to specific ionic channels; their findings on the thermal capacitance increase have been supported by experiments from several additional groups [19,20,[23][24][25]. Shapiro et al [16] also developed a theoretical model where the temperature elevation was seen to give rise to membrane capacitance increase at the membrane's boundary regions (see also Liu et al [26] and Rabbit et al [27]). However, as recently pointed out in our reanalysis of this theoretical model [28,29], upon correcting a mathematical convention error it actually predicts a net capacitance decrease, contrary to the experimental measurements.…”
Section: Introductionmentioning
confidence: 99%
“…It has been argued previously that IR heat pulses directly evoke synaptic vesicle release in addition to modulating ion channel conductance and capacitive depolarization (Rajguru et al, 2011;Liu et al, 2014;Rabbitt et al, 2016). Therefore, the expected changes in sensitivity to IR heat pulses after BX administration would be less than the changes in sensitivity to mechanical stimulation.…”
Section: B B B B B B B B B B B B B B B B B B B B B B B B B B B B B mentioning
confidence: 96%